Public Knowledge and Private Gain: The Effect of Spillover Networks on Firms' Innovative Performance - Erna Herlina; Rusman Ali; Fuadi Fuadi (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This research cores around presenting the idea of an overflow organization, to be specific an organization of source organizations whose public information is a getting organization that can be ingested and utilized as advancement input. The review was led utilizing patent-put together information with respect to a board of semiconductor organizations somewhere in the range of 1976 and 2002. The outcomes show that the imaginative presentation of the organization will in general be higher when the overflow network is plentiful or wealthy in underlying openings. Notwithstanding, great overflow organizations and opening wealth are primary for the most part counterproductive. It is steady with information that the worth of outer information inputs relies upon the venture level assets that can be pooled. Organizations benefit from overflow networks that rely upon specific variables, specifically intraorganisasi logical force and level of incorporation into (downstream).